Perancangan Media Pembelajaran Berbasis Android pada Mata Pelajaran Geografi di SMAN 1 Ampek Angkek Kabupaten Agam - Maulana, Khalid; Sesmiarni, Zulfani; Zakir, Supratman; M, Iswantir (Indonesian Research Journal on Education, 2022)
The purpose of this study was to design learning media for geography subjects at SMAN 1 AmpekAngkek. The results of interviews with teachers of geography subjects that so far the learning process for students is still using conventional methods, namely the teacher explains with lectures followed by using blackboard media and students listen to textbooks during learning. Because this method causes learning to be ineffective, uninteresting, and slow to understand, it has an impact on students' understanding and learning abilities. Meanwhile, some students stated that geography is one of the most difficult lessons at SMAN 1 Ampek Angkek, especially in the social studies department. This study uses the ADDIE version of the Research and Development (R&D) method, as well as the Luther-Sutopo version of the Multimedia Development Life Cicle development model. The product test used in this research is the product validity test using the Aiken's V statistic formula, the product practicality test using the Moment Kappa formula and the product effectiveness test using the Richard R. Hake statistic formula (G-Score). The results of the product test that the author conducted obtained the validity test of 3 appraisers, obtained a value of 0.78 with valid criteria, the practicality test of 2 appraisers obtained a value of 1.00 with very high criteria, and the effectiveness test of 10 appraisers obtained a value of 0.92 with effective criteria.